Prevention and management of immune-related adverse events for biliary tract cancers - LIU Kun, GUO Wei (Waike lilun yu shijian, 2025)
Immune checkpoint inhibitors (ICIs) combined with chemotherapy has become the first-line standard treatment for advanced biliary tract cancers (BTC). However, the application of ICIs comes with its risks of immune-related adverse events (irAEs). BTC patients often face greater challenges in the diagnosis and management of irAEs, especially in the differential diagnosis of immune related hepatitis, due to the presence of special conditions such as underlying liver dysfunction and biliary obstruction. We aimed to systematically review the current status of BTC immunotherapy, the spectrum of irAEs, clinical characteristics, prevention strategies, and management principles. We focused to investigate the specificity and response measures of irAEs management in BTC patients, optimizing immunotherapy management for BTC patients, maximizing treatment benefits and ensuring patient safety, and exploring the future research directions.